Estudos fitogeográficos na bacia hidrográfica do arroio Lajeado Grande - oeste do RS - Alves, Fabiano da Silva (2008)
Phytogeographical studies that seek to understand how was the colonization and distribution of native vegetation in the territory do Rio Grande do Sul State, back since the end of the XIX century. However, currently, there is still no consensus with regard to different types shows that the vegetation in the state, nor about the terminology to be used more generally. When dealing specifically with the West and Southwest regions, the theme, "Phytogeography" is of utmost importance, therefore still has no points and clarified in the scientific literature. Facing this situation, the phytogeographical studies in the basin hydrographic the Lajeado Grande stream- west of the RS has as its main objective, to contribute to the advancement of knowledge phyto-geographic South Rio-Grandense. For that, initially, was made an analysis in terms of the physical environment, where they were recognized and differentiated, morpholithological units, based on the characteristics of the relief, of the substrate rocky and soils. These units were represented on the morpho-lithological map, which served as a geographical basis to achieve the floristic survey. Developed under the physiognomic and ecological aspect, this survey revealed the existence of different types in native vegetation. Since then, a study was conducted correlative between vegetation and physical environment in order to identify the factors that influence the environment in floristic composition and spatial distribution of vegetation cover. This correlation showed that all types, in the area under study, have close relations with the physical environment, presenting a "pattern" of geographic distribution. In certain situations, such relationships are so strong that two phanerophytas species were defined as "geo-indicators" of substrate rocky. The results in this study were represented in phyto-geographic map, defined from the types of vegetation in relation to the units morpho-lithological, and differentiated into: campos (grassland) in sandstone hills, campos with curupi (Sapium haematospermum Müll. Arg. Euphorbiaceae) in sandstone hills, campos with butiá-anão (Butia lallemantii Deble & Marchiori Arecaceae) in sandstone hills, campos in volcanic hills, campos with espinilhos (Acacia caven (Molina) Molina - Leguminosae ou Fabaceae) in volcanic hills, vegetation of cornijas (steps in middle rocky slopes), vegetation of morrotes (hills with slopes) of sandstone, capão (forest) of forest and the gallery forest. It is hoped that this work will serve as an allowance for future studies and proposals for conservation and preservation of biodiversity and natural landscapes in Rio Grande do Sul state.